Electrical Analogy to an Atomic Force Microscope - Kucera, Ondrej (Společnost pro radioelektronické inženýrství, 2010)
Several applications of the atomic force microscopy (AFM), such as measurement of soft samples, manipulation with molecules, etc., require mechanical analysis of the AFM probe behavior. In this article we suggest the electrical circuit analogy to AFM cantilever tip motion. Well developed circuit theories in connection with fairly accessible software for circuit analysis make this alternative method easy to use for a wide community of AFM users.
Keywords: Atomic Force Microscopy; electrical mechanical analogs; circuit theory